PEMANFAATAN UBI JALAR DALAM PEMBUATAN BAKSO PELANGI - Imelda Siska; Yoshi Lia Anggrayni; Dihan Kurnia; Pajri Anwar; Jiyanto Jiyanto (Jurnal Pengabdian Kepada Masyarakat, 2022)
This event is aimed to provide knowledge to community members of Tanjung Medang village about the technology of processing livestock products and to provide knowledge about one of livestock product management thoroughly to the quality of being kind. This event has been in the Tanjung Medang village hall, Kuantan Singingi district, Riau. The result of this event is increase in knowledge and skill the community, and intertwining cooperation state of the lecturers, students and citizens in developing technology especially a field of agriculture and livestock in particular. Expected the event will be the establishment of cooperation are continuing between universities and community.